2015
DOI: 10.1002/aenm.201500377
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Mixed Ionic Electronic Conduction in La0.8Sr0.2MnO3+δ Nanostructures through Fast Grain Boundary Oxygen Diffusivity

Abstract: Nanoionics has become an increasingly promising field for the future development of advanced energy conversion and storage devices, such as batteries, fuel cells, and supercapacitors. Particularly, nanostructured materials offer unique properties or combinations of properties as electrodes and electrolytes in a range of energy devices. However, the enhancement of the mass transport properties at the nanoscale has often been found to be difficult to implement in nanostructures. Here, an artificial mixed ionic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
94
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 40 publications
11
94
1
Order By: Relevance
“…For both LSCF films, the dominant crystalline orientation is confirmed to be (100) (pseudocubic notation). smooth transition at the interface may be due to the presence of a high concentration of defects which would facilitate ion transport and diffusion [6,16]. Detailed analyses of the two types of LSCF microstructure are currently being performed and results will be reported in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For both LSCF films, the dominant crystalline orientation is confirmed to be (100) (pseudocubic notation). smooth transition at the interface may be due to the presence of a high concentration of defects which would facilitate ion transport and diffusion [6,16]. Detailed analyses of the two types of LSCF microstructure are currently being performed and results will be reported in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have also shown that engineering of lattice strain in oxygen ion conductors via heterostructures could lead to significant increases in ionic conductivity [3][4][5]. Studies have further demonstrated enhanced oxygen diffusion mediated by grain boundaries, suggesting the enhancement of mass and charge transport properties in such intrinsic interfaces [6][7]. However, systematic comparison from sample to sample is complicated by the fact that controlling the density and size of grains usually entails modifying the film deposition parameters which would invariably affect its corresponding properties.…”
Section: Introductionmentioning
confidence: 99%
“…8 To overcome the leakage current issue, the mixed-ionicelectronic conduction (MIEC) selector was developed by IBM. 10,11 The MIEC is widely accepted as a nearly ideal selector because it shows low off-current (100 pA), high on-current (10 μA) and steep subthreshold swing characteristics (o60 mV per decade). However, its conduction mechanism is not clearly understood, and its reliability has not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Even compared with the conventional intermediate temperature cathode materials, the LSM-BZY cathode in our study shows both smaller electrode polarization resistance and larger fuel cell power output. It has been recently reported that the oxygen diffusion and electrocatalytic activity of LSM are improved at the grain boundary of nanocrystalline films at low temperature [50,51]. One can speculate that this happened also at the surface of LSM nanoparticles, explaining the outstanding increase in power performance.…”
Section: Discussionmentioning
confidence: 89%